The Effect of Eye Contact Is Contingent on Visual Awareness - Xu, Shan; Zhang, Shen; Geng, Haiyan (Frontiers in Psychology, 2018)
The present study explored how eye contact at different levels of visual awareness influences gaze-induced joint attention. We adopted a spatial-cueing paradigm, in which an averted gaze was used as an uninformative central cue for a joint-attention task; prior to the onset of the averted-gaze cue, either supraliminal (Experiment 1) or subliminal (Experiment 2) eye contact might be presented. The results revealed a larger subsequent gaze-cueing effect following the supraliminal eye contact, compared to a no-contact condition. Nevertheless, the gaze-cueing effect was reduced by the subliminal eye contact, in comparison to the no-contact condition. These findings suggest that the facilitation effect of eye contact on coordinating social attention depends on visual awareness, and that the subliminal eye contact might have a distinct impact on subsequent social attention processes, different from that of supraliminal eye contact. This study highlights the need for further investigation on the role of eye contact in implicit social cognition.